EVALUATING A PHARMACIST-NURSE TEAM APPROACH TO POLYPHARMACY MANAGEMENT IN OLDER ADULT PRIMARY CARE PATIENTS - Mohammed Nasser Matar Alanaz, Khalid Nowaf Alenazy, Raja Awwadh Almutairi, Adel Shafi Alanazi, Meshal Twairesh Alshammari, Majed Ahmed Alshammari, (Chelonian Research Foundation, 2022)
Polypharmacy, defined as concurrent use of multiple medications, is increasingly prevalent among older adults and associated with adverse drug effects, medication non-adherence, and increased healthcare utilization. Collaborative pharmacist-nurse models have been proposed to optimize safe medication use. This study aimed to implement and evaluate a pharmacist-nurse collaborative medication management clinic integrated into primary care clinics targeting older adults at high-risk from polypharmacy. A randomized controlled trial was conducted among 150 patients aged ≥65 years taking ≥10 scheduled medications randomized to the intervention or usual care. The pharmacist-nurse clinic utilized pharmacist-led medication reconciliation, regimen review, deprescribing, caregiver education, and nurse care coordination. Outcomes assessed at 6 months included number of medications, medication appropriateness, 30-day medication-related hospital readmissions, and cost. Patients in the intervention group exhibited significantly greater reductions in the number of scheduled medications (-2.5 vs. -0.3 medications, p<0.001) and improvements in medication regimen appropriateness assessed using the Medication Appropriateness Index (MAI score 65% vs. 54%, p=0.02) compared to usual care. The intervention was also associated with lower medication-related hospital readmissions within 30 days (6% vs. 15%, p=0.04). No significant difference was observed in cost. Results demonstrate implementation of a pharmacist-nurse collaborative medication management clinic is an effective approach to polypharmacy management with clinical and utilization benefits for high-risk older adult primary care patients.